Cross-linking Process, Mechanical Properties and EMI Absorption Shielding Efficiency of Composites Based on NBR - Ján Kruželák; Andrea Kvasnicakova; Michaela Džuganová; Rastislav Dosoudil; Ivan Hudec (Current Approaches in Engineering Research and Technology Vol. 8, 2024)
The rapid progress in industrialization and informatization of modern society has led to the generation of high amounts of environmental pollution, especially from electromagnetic radiation. Electromagnetic interference can be explained as the undesired disturbances in electronic appliances, which are caused by interference of multiple electromagnetic signals transmitting from neighboring devices. Acrylonitrile-butadiene rubber (NBR) is one of the most widely used specialty type rubber with a good correlation between cost and properties. Due to its polar character, it has good resistance to oils and non-polar solvents. Two types of composites were tested for electromagnetic interference absorption shielding performance, cross-linking process and physical-mechanical properties. Manganese-zinc ferrite, nickel-zinc ferrite, and both fillers in their mutual combinations were incorporated into acrylonitrile-butadiene rubber. The overall content of the filler, or fillers combinations was kept at 200 phr. Carbon black, or carbon fibres, respectively were incorporated into each rubber formulation in constant loading - 25 phr. The work was focused on the understanding of correlation between electromagnetic shielding parameters and electrical conductivity of composites in relation to their absorption shielding effectiveness. The absorption shielding ability of materials was evaluated within the frequency range from 1 MHz to 6 GHz. The study revealed a good correlation among permittivity, conductivity, and EMI absorption shielding. The higher the conductivity, the higher the permittivity, resulting in the lower absorption shielding performance. The higher the ratio of nickel-zinc ferrite in magnetic filler combinations, the lower the conductivity and permittivity and the higher the absorption shielding. The experimentally obtained data also revealed that the influence of the type of ferrite or ferrites combinations on curing parameters and physical-mechanical properties was negligible.